Oral Supplementation of Ozonated Sunflower Oil Augments Plasma Antioxidant and Anti-Inflammatory Abilities with Enhancement of High-Density Lipoproteins Functionality in Rats - Kyung-Hyun Cho; Ji-Eun Kim; Myeong-Sung Lee; Ashutosh Bahuguna (MDPI AG, 2024)
Research on ozonated sunflower oil (OSO) is mostly restricted to its topical application, whereas the functional and toxicological assessment of oral OSO consumption is yet to be solved. Herein, OSO was orally supplemented in rats to assess the impact on plasma antioxidant status, low-density lipoproteins (LDL), and high-density lipoproteins (HDL). Also, the functionality of HDL from the OSO-supplemented rats (OSO-HDL) was tested against carboxymethyllysine (CML)- induced hyperinflammation in embryo and adult zebrafish. The results revealed that four weeks of OSO supplementation (3 g/kg BW/day) had no adverse effect on rats' hematological and blood biochemical profiles. Nonetheless, decreased interleukin (IL)-6, and LDL-C levels, along with enhanced ferric ion reduction ability (FRA) and sulfhydryl content, were observed in the plasma of OSO-supplemented rats compared to the control and sunflower oil (SO) supplemented group. In addition, OSO supplementation stabilized apoA-I/HDL and augmented HDL-allied paraoxonase (PON)-1 activity. The microinjection of OSO-HDL (10 nL, 2 mg/mL) efficiently prevented the CML (500 ng)-induced zebrafish embryo mortality and developmental deformities. Similarly, OSO-HDL thwarted CML-posed neurotoxicity and demonstrated a significant hepatoprotective effect against CML-induced fatty liver changes, hepatic inflammation, oxidative stress, and apoptosis, as well as exhibiting a noticeable influence to revert CML-induced dyslipidemia. Conclusively, OSO supplementation demonstrated no toxic effects on rats, ameliorated plasma antioxidant status, and positively influenced HDL stability and functionality, leading to a protective effect against CML-induced toxicity in zebrafish.